Acute Kidney Injury and Hyponatremia in Ultra-Trail Racing: A Systematic Review - Lecina, M.; Castellar-Otín, C.; López-Laval, I.; Carrasco Páez, L.; Pradas, F. (Medicina, 2022)
Background and objectives: Ultra-trail races can cause episodes of acute kidney injury (AKI) and exercise-associated hyponatremia (EAH) in healthy subjects without previous renal pathology. This systematic review aims to review the incidence of these two syndromes together and separately taking into account the length and elevation of the ultra-trail race examined.